Crystal growth, optical, thermal and piezoelectric properties of HoCa4O(BO3)3 crystal. Issue 37 (6th September 2021) - Yu, Pingzhang; Pan, Xiaobo; Wu, Guangda; Liu, Yanqing; Yu, Fapeng; Wang, Zhengping; Xu, Xinguang
Abstract : High-quality crystals of HoCa4 O(BO3 )3 were grown by the Czochralski method. The optical, thermal and piezoelectric properties were investigated. Abstract : Large size HoCa4 O(BO3 )3 (HoCOB) crystal was successfully grown by the Czochralski (Cz) method. Through single-crystal X-ray diffraction the cell parameters were determined to be a = 8.090(3) Å, b = 16.018(7) Å, c = 3.5317(14) Å, β = 101.28°(4) and Z = 2 with the space group Cm . The Archimedes method was used to measure the density which was 3.85 g cm −3 . In the transmittance spectrum of HoCOB, there are strong absorption peaks from 200 to 680 nm and 1800 to 2200 nm, corresponding to the Stokes levels between 13 219 and 49 335 cm −1 . The thermal and the piezoelectric properties were investigated under different temperatures. At 300 K around, the thermal expansion coefficient, thermal conductivity, specific heat, and relative dielectric constant on the b axis direction ( i.e. the unique two-fold axis direction) were 5.35 × 10 −6 K −1, 2.18 W m −1 K −1, 0.58 g −1 K −1, and 12.5, respectively.